From Hinduism to Hindutva: civilizational internationalism and UNESCO. (6th March 2023) - Singh, Rani; Winter, Tim
Abstract : This article examines the political appropriation of heritage in India. It demonstrates how India's civilizational discourses circulate at the international level through UNESCO in benign ways and yet, simultaneously, advance the populist politics now familiar to the Hindutva movement. Abstract: This article considers civilizational politics at the interface between nationalism and internationalism. It does this by focusing on some key trends in India's engagements with UNESCO and its flagship conventions for culture. The article builds on existing scholarship regarding the political appropriation of key religious and heritage sites within India by critically examining how Hinduism is presented to UNESCO and other organizations as a religious and civilizational heritage for global recognition and endorsement. We argue that UNESCO's programmes and conventions are being co-opted via a rewriting of history and in the creation of heritage imaginaries of a Hindu nation. From there, the discussion extends previous critiques regarding the conjoining of Hinduism to a Harappan civilization heritage by showing how this geographically extends outwards via a programme of Indian Ocean diplomacy conceived around environmental and historical connectivities. In pulling these various threads together, the article demonstrates the ways in which Hindu civilizational discourses circulate at the international level in seemingly benign and banal ways, and, yet, simultaneously advance the domestic cultural politics now familiar to the Hindutva movement.